Iron Man: Non-HFE Hemochromatosis Without Significant Fibrosis. Issue 1 (25th January 2023) - Chaudhry, Hunza; Sohal, Aalam; Petrosyan, Arpine; Laput, Gieric; Roytman, Marina; Prajapati, Devang
ABSTRACT: Hemochromatosis is a genetic disorder marked by abnormally high levels of intestinal iron absorption leading to severe end-organ damage. It is classically associated with HFE gene mutations, including C282Y and H63D, but in recent years, many non-HFE mutations along with novel variants have been discovered, particularly among non-Whites. We describe a case of an elderly Japanese patient who was evaluated for markedly elevated ferritin found to have hemochromatosis, with no hepatic fibrosis while being negative for HFE and common non-HFE gene mutations.